Media Development Using Macromedia Flash 8 on the Material of the Dynamics of Planet Earth - Lilis L. Yusup; Sunarty S. Eraku; Daud Yusuf (International Journal of Innovation and Education Research, 2023)
This research was conducted at SMA Negeri 1 Limboto. This research aims to develop learning media using macromedia flash 8 on the material of planetary dynamics. The method used in this research is the ADDIE method. Data collection techniques through observation, interviews, questionnaires and documentation. The instrument used in the form of assessment criteria to determine the feasibility of media from material experts, material experts, and geography teachers as well as student responses to learning media using a questionnaire. The data collected in the form of research results regarding the quality of the media get a value of 68.23% with the level of validity included in the qualification "valid", the results of validation by material experts get a value of 86.66% with the level of validity included in the qualification "very valid", and the results of validation by geography teachers get a value of 80.18% with the level of validity included in the qualification "very valid", while for student responses from the results of the trial get a value of 85%, this value is in the category "strongly agree".